A participant-focused sociological analysis of Beedz, a Grahamstown skills training project for women - Bobo, Azola Benita Dorothea (Rhodes University, Faculty of Humanities, Department of Sociology, 2017)
This research looked at a participant-focused sociological analysis of Beedz, a Grahamstown skills training project for women. Beedz is run by the River of Life Church and aims to equip women with the necessary skills to participate in the economy, either as entrepreneurs or as employees. Using third world feminist theory, this research explored the experiences of women who have participated in the Beedz programme, what they went through, and whether the programme benefited them or not. In particular, this research explored how the participants experienced Beedz as a programme for women without an exclusive focus on traditional feminist issues. This research was qualitative in nature; with in-depth, semi-structured interviews being used as a means of data collection. Data was analysed using key themes emerging from the interviews. The key findings of this research were that it is important to include women in training projects, as by including them you create spaces and enabling environments for women to empower themselves. Secondly, although Beedz does not deliberately work from the third world feminist theory, it could be argued that it fits in this framework as this programme facilitates skills training through looking at women as a whole, taking into account not only their gender, but also their class and race. Recommendations were made on how the Beedz programme may be improved, based on the information gathered from the participants from the interviews conducted during the research, with the key recommendation being that the organisers of the programme need to create a space for the participants' voice to be heard, so that the programme can be relevant and beneficial to them.
Keywords: Beedz (Makhanda, -- South Africa); Feminist theory -- Developing countries; Training -- South Africa -- Makhanda; Occupational training -- South Africa -- Makhanda; Women -- South Africa -- Makhanda -- Social conditions